2023
DOI: 10.3389/fnut.2023.1171216
|View full text |Cite
|
Sign up to set email alerts
|

Serum 25-hydroxyvitamin D as a predictive biomarker of clinical outcomes in patients with primary membranous nephropathy

Abstract: BackgroundPrimary membranous nephropathy (PMN) is an immune-related disease with increased morbidity and the most common cause of adult nephrotic syndrome (NS). The serum 25-hydroxyvitamin D [25(OH)D)], a biomarker of vitamin D (VD) status, tends to decline in patients with kidney disease. However, the relationship between 25(OH)D and PMN is still unclear. Therefore, this study aims to clarify the association between 25(OH)D and disease severity and therapy response of PMN.MethodsA total of 490 participants di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…Gholami et al, also in a meta-analysis of prospective-cohort studies in which they analyzed this association, also found the protective role of serum 25-hydroxyvitamin D in the cardiovascular system, noting the need for extensive evaluation also according to the sex of patients [ 52 ]. Regarding specificity, for example, purposes, we mention that positive associations were also found between the negative prognosis of primary membranous nephropathy and low levels of serum 25-hydroxyvitamin D, being considered a potential marker in this regard as well [ 53 ]. Also, 25-hydroxyvitamin D is considered a potential biomarker of sickle cell disease, given its positive correlation with hemolysis markers [ 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…Gholami et al, also in a meta-analysis of prospective-cohort studies in which they analyzed this association, also found the protective role of serum 25-hydroxyvitamin D in the cardiovascular system, noting the need for extensive evaluation also according to the sex of patients [ 52 ]. Regarding specificity, for example, purposes, we mention that positive associations were also found between the negative prognosis of primary membranous nephropathy and low levels of serum 25-hydroxyvitamin D, being considered a potential marker in this regard as well [ 53 ]. Also, 25-hydroxyvitamin D is considered a potential biomarker of sickle cell disease, given its positive correlation with hemolysis markers [ 54 ].…”
Section: Resultsmentioning
confidence: 99%